Factors Associated with the Selection of Contraceptive Implants for Family Planning Acceptors in Jambi City - Enny Susilawati; Neny Heryani; Lia Artikasari; Erni Pransiska (STIKes Hang Tuah Pekanbaru, 2021)
In several decades, based on the results of the census, Indonesia has experienced significant population growth. In the last ten years, the population has increased by 32.56 million. The KB I program was initiated to reduce the birth rate by using several methods, one of which is the hormonal contraceptive implant method. However, data from the Jambi health office shows that there are still quite a few family planning acceptors who use implant contraceptives, even though it is known that this type of contraception is very effective, with a long duration of use, and an affordable price. This study aims to analyze what factors are related to the choice of implant type contraceptives for family planning acceptors in the work area of ​​Putri Ayu Health Center, Jambi City. This type of research is analytic Observational with a cross sectional design. The population of this study was 3,029 people. Samples were taken by quota sampling as many as 96 respondents. Data collection was carried out using a questionnaire. Data analysis was carried out bivariately using the chi square test with a significance level of 0.05. The data collected is based on research variables, namely knowledge, attitudes, perceptions, and motivations of family planning acceptors. The results of Chi Square analysis showed that knowledge with p-value 0.002, attitude p-value 0.224, perception p-value 0.173, and motivation with p-value 0.005. Factors related to the selection of contraceptive implants for mothers of family planning acceptors in the working area of ​​Putri Ayu Health Center are knowledge and motivation